Lower limb coordination patterns following anterior cruciate ligament reconstruction: A longitudinal study - Cortney Armitano-Lago; Elizabeth Bjornsen; Caroline Lisee; Ashley Buck; Christin Büttner; Adam W. Kiefer; Todd A. Schwartz; Brian Pietrosimone (Journal of Sport and Health Science)
Background: Changes in lower limb joint coordination have been shown to increase localized stress on knee joint soft tissue—a known precursor of osteoarthritis. While 50% of individuals who undergo anterior cruciate ligament reconstruction (ACLR) develop radiographic osteoarthritis, it is unclear how underlying joint coordination during gait changes post-ACLR. The purpose of this study was twofold: to determine differences in lower limb coordination patterns during gait in ACLR individuals 2, 4, and 6 months post-ACLR and to compare the coordination profiles of the ACLR participants at each timepoint post-ACLR to uninjured matched controls. Methods: We conducted a longitudinal assessment to quantify lower limb coordination at 3 timepoints post-ACLR and compared the ACLR coordination profiles to uninjured controls. Thirty-four ACLR (age = 21.43 ± 4.24 years, mean ± SD; 70.59 % female) and 34 controls (age = 21.42 ± 3.43 years; 70.59% female) participated. The ACLR group completed 3 overground gait assessments (2,4, and 6 months post-ACLR), and the controls completed one assessment, at which lower limb kinematics were collected. Cross-recurrence quantification analysis was used to characterize sagittal and frontal plane ankle-knee, ankle-hip, and knee-hip coordination dynamics. Comprehensive general linear mixed models were constructed to compare between-limb and within-limb coordination outcomes over time post-ACLR and a between-group comparison across timepoints. Results: The ACLR limb demonstrated a more “stuck” sagittal plane knee-hip coordination profile (greater trapping time (TT); p = 0.004) compared bilaterally. Between groups, the ACLR participants exhibited a more predictable ankle-knee coordination pattern (percent determinism (%DET); p < 0.05), stronger coupling between joints (meanline (MNLine)) across all segments (p < 0.05), and greater knee-hip TT (more “stuck”; p < 0.05) compared to the controls at each timepoint in the sagittal plane. Stronger frontal plane knee-hip joint coupling (MNLine) persisted across timepoints within the ACLR group compared to the controls (p < 0.05). Conclusion: The results indicate ACLR individuals exhibit a distinct and rigid coordination pattern during gait compared to controls within 6-month post-ACLR, which may have long-term implications for knee-joint health.